Makna dan Kedudukan Hukum Naskah Proklamasi 17 Agustus 1945 dalam Sistem Ketatanegaraan Republik Indonesia - Jazim Hamidi (Fakultas Hukum Universitas Mulawarman, 2006)
The meaning of proclamation text is about Indonesian independence proclamation. While the nature of free nation are free from all kinds of shackles of colonialist (imperialism), free and independen to decide, to regulate, and to manage a state according to constitutional objective. Legal status of proclamation text in “Stufenbautheorie” perspective: Proclamation text could not qualificier as Grundnorm as Kelsen mean. For Indonesia case, values, nature, and principes which contain in proclamation text has legal status as Grundnorm. It is as a source of all sources of law and stand in out of legal system (meta juristic). All people must appriciate and obey to the Proclamation Text and Constitution.. Proclamation text could not qualificier as Staatsfundamentalnorm as Nawiasky mean. For Indonesia case, the Preamble of the Constitution of 1945 as Staatsfundamentalnorm and inside it there are Proclamation and Pancasila value. Legal implication of it the proclamation text as a source of inspiration, base, and critical norm for legal drafting and policy of nation and state. Key words: the meaning and legal status of proclamation text (makna dan kedudukan hukum naskah proklamasi), the republic of Indonesia’s constitutional system (sistem ketatanegaraan Republik Indonesia).